In the woods - French, Tana (New York : Penguin Books, 2008)
Detective Rob Ryan and his partner, Cassie Maddox, investigate the murder of a 12-year-old girl near a Dublin suburb. The case resonates with similarities to a murder committed twenty years before that involved two children and the young Ryan.
Keywords: Ryan, Rob (Fictitious character); Maddox, Cassie (Fictitious character); Detectives -- Ireland -- Dublin; Women detectives -- Ireland -- Dublin; Murder -- Investigation; Children -- Crimes against; Mystery fiction; Psychological fiction